To Cheat or not to Cheat? Sex Differences and Academic Performance as Factors of Cheating Behavior - Hadjar, Ibnu (Sawwa: Jurnal Studi Gender, 2019)
Cheating behavior at higher education is a global phenomenon since it is found at any university in any country. This study is to examine whether sex differences and academic performance reflect the different likelihood of doing cheating among students. Using a questionnaire, data were collected from 436 students selected from different semesters and study programs in all faculties at a State Islamic University. Data were analyzed by using logistic regression, both separately and simultaneously. The results of data analysis revealed that male students tend to be more likely to do cheating categories than that of their female counterparts. It also found that academic performance affects negatively the likelihood of students to cheat in three categories of cheating behavior, but not in the other three. There is no stimulant effect of sex and academic performance on the likelihood of all categories of cheating behaviors. In other words, the effect of sex differences is not depended on academic performance and vice versa.